Perceptions of animal experimentation: a longitudinal survey with veterinary students in Araçatuba, São Paulo, Brazil - Machado, Gisele F. [UNESP]; Melo, Guilherme D. [UNESP]; Perri, Silvia H. V. [UNESP]; Fernandes, Fernando V. [UNESP]; Moraes, Olívia C. [UNESP]; Souza, Milena S. [UNESP]; Grano, Fernanda G. [UNESP]; Silva, José E. S. [UNESP]; Nunes, Cáris M. [UNESP] (Taylor & Francis, 2017)
Animal experimentation is a controversial topic, especially among the general public and the scientific community. Thirty-eight undergraduate students attending the College of Veterinary Medicine–São Paulo State University in the municipality of Araçatuba, São Paulo, Brazil, were followed up between 2008 and 2011 and were asked to complete an annual questionnaire focused on different aspects of animal experimentation, including the animal species involved, the objectives of the research, ethics, animal welfare and euthanasia. Most students agreed that animal testing is not morally incorrect, and the dynamics of students’ attitudes were notable: undergraduates tended to change their opinion over time, with junior students opposing animal experimentation more than seniors do, indicating that the more scientific knowledge the students acquire, the more favourable to animal experimentation they become. Nevertheless, they agreed that research must consider the basic principles of animal welfare.
Keywords: Animal welfare; euthanasia; laboratory animals; questionnaires; veterinary education